Current status and recent dynamics of the Black Brant Branta bernicla breeding population - Sedinger, James S; Lensink, Calvin J; Ward, David H; Anthony, Michael; Wege, Michael L; Byrd, G Vernon (Wildfowl, 1993)
We summarize current knowledge about the distribution of Pacific Black Brant and recent dynamics of colonies, particularly on the Yukon-Kuskokwim (Y-K) Delta, Alaska. About 20,000 nests are required to produce the number of young in the autumn flight using estimates of clutch size, hatching success and gosling survival based on colonies on the Y-K Delta. More than 80% of the nests in the population can be accounted for currently on the Y-K Delta. Most moulting individuals that did not breed, or were unsuccessful, are unaccounted for in late summer. Numbers of Black Brant nesting in major colonies on the Y-K Delta declined >60% in the early 1980s, most likely as a result of local subsistence harvest combined with predation by arctic foxes. Effective management of this population requires a better understanding of the distribution of breeding and moulting birds, the importance of breeding habitat to colony dynamics and the role of both sport and subsistence harvest in population dynamics.